SEJARAH DAKWAH LEMBAGA DAKWAH ISLAM INDONESIA (LDII) DI KOTA JAMBI 1995 – 2020 - Hendra Gunawan; Efriadi Efriadi; Syamsu Hadi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
This study is motivated by the existence of a negative public stigma against LDII in Jambi City, but LDII da'wah activities in Jambi City still exist. Therefore, the researchers tried to narrate more about the history of LDII in Jambi City in 1995-2020. The problems discussed in this study are the history of the establishment of LDII in Jambi City; da'wah conducted by LDII in Jambi City in 1995-2020; and people's views on LDII in Jambi City. To answer these problems, the researchers used historical research methods with heuristic stages, data verification, interpretation and historiography. The findings show that in 1979 LDII entered Jambi and was brought by Hamit Hoyyan under the name Lemkari. Experiencing developments since the foundation was founded in 1995, although 2020 was a bit of a challenge due to the pandemic, LDII activities still exist. Da'wah is carried out through recitation, education, websites and magazines. There are positive and negative public responses to LDII.